Constructing artworks - Alessandro Jedlowski (Nordic Journal of African Studies, 2008)
This essay focuses on Seydou Keïta’s work, and on the way in which this work has been received and conceptualized within both the African and the Western context. These photographs have a long history of geographical and cultural displacement that has deeply influenced their status, as well as the status of the people who engaged with them. The essay follows the development of this history, dealing with the processes of construction of Seydou Keïta as an author and of his photographs as international acclaimed pieces of art.